PENGARUH PENERAPAN BUDAYA ORGANISASI DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA KARYAWAN PADA RUMAH SAKIT JIWA TAMPAN PROVINSI RIAU - Herlen Syafira; Kasmiruddin " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
The purpose of this study was to determine and analyze the application of organizational culture and work motivation to employee job satisfaction at the handsome mental hospital in Riau province partially and simultaneously. The method used in this research is a quantitative descriptive method with the SPSS program. This research was conducted at the Tampan Hospital in Riau Province, which is located on Jl. HR. Soebrantas, Km 12.5, Simpang Baru, Handsome District, Pekanbaru City, Riau, with a total of 75 employees as respondents. This study uses several analytical tests, namely: validity test, reliability test, multiple linear regression analysis test, coefficient of determination test, simultaneous test, and partial test. The results showed that testing the hypothesis of the application of organizational culture and work motivation had a significant effect on employee job satisfaction at the RSJT Riau Province, this was shown based on the value of T_count > T_table, and the results of the F test from the application of organizational culture and work motivation had a significant effect on employee job satisfaction in RSJT Riau Province, shown based on the value of F_count 15,894 > T_table 3,12. Keywords: Implementation of Organizational Culture, Work Motivation, and Job Satisfaction